Differential Outcomes Training Ameliorates Visual Memory Impairments in Patients With Alzheimer’s Disease: A Pilot Study - Carmona, Isabel; Vivas, Ana B.; Estévez, Angeles F. (Frontiers in Psychology, 2019)
It is well known that Alzheimer’s disease (AD), the most common form of dementia, is associated with deficits in cognitive processes including visual memory impairments. One technique that might be used to ameliorate these impairments is the differential outcomes procedure (DOP) that involves associating each to-be-remembered stimulus with a specific outcome. Objective: Previous research has demonstrated that the DOP can be used to reduce or eliminate the learning and memory deficits associated with animal models of amnesia and dementia (Savage, 2001). Furthermore, this procedure has been shown to improve delayed facial recognition in healthy older adults as well as in patients diagnosed with AD. The main aim of the present study is twofold; extend these findings to other type of visual stimulus, and to investigate the effect of the DOP in memory retention in AD patients. Method: Ten patients diagnosed with AD and ten healthy controls participated in this study. The experiment included two phases. In the first one, they had to perform a delayed matching-to-sample task. In the second phase, participants performed a recognition memory task, designed to assess long-term retention, 1 hour and1 week after the training. Results: Participants showed a better memory-based performance as well as a higher long-term retention of the information when trained under the differential outcomes condition, relative to the non-differential outcomes procedure condition. Conclusions: The DOP seems to be an effective, easy to implement, technique to enhance visual memory in AD patients.